“DETERMINANTS OF AUDIT FIRMS SWITCHING AMONG INDONESIAN PUBLIC COMPANIES” - Maya Kirana Putri (Jurnal Ilmiah Mahasiswa FEB, 2017)
The study aims to examine the factors influencing to audit firms switching in Indonesia. These factors are management turnover, size of the client’s firm, client’s complexity and client’s growth. Research samples are selected by purposive sampling method of 100 public companies listed in Indonesian Stock Exchange. Logistic regression analysis is employed to test the hypothesis. The research result reveals that management turnover and client’s growth positively affect towards audit firms switching. Otherwise, the size of the client’s firm and client’s complexity did not affect to audit firms switching because large companies attempt to avoid public’s perception that by switching the audit firms means the company is experiencing financial difficulties, and it takes time for the new audit firms to understand well the state of client’s company if switching is occurred.Keywords: audit firms switching, management turnover, size of the client’s firm, client’s complexity, client’s growth